2021
DOI: 10.3390/ijms22052454
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemistry of Phytocannabinoids and Metabolic Engineering of Their Production in Heterologous Systems

Abstract: The medicinal properties of cannabis and the its legal status in several countries and jurisdictions has spurred the massive growth of the cannabis economy around the globe. The value of cannabis stems from its euphoric activity offered by the unique phytocannabinoid tetrahydrocannabinol (THC). However, this is rapidly expanding beyond THC owing to other non-psychoactive phytocannabinoids with new bioactivities that will contribute to their development into clinically useful drugs. The discovery of the biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 88 publications
(172 reference statements)
0
33
1
Order By: Relevance
“…In general, PT1 and PT4 are similarly regulated during female flower maturation in the same variety but the regulation is temporally different. The superimposition suggests that PT1 instead of PT4 more correlates with CBG content, which is not consistent with the recent findings (Blatt-Janmaat & Qu, 2021). Further analysis of these two enzymes will be more explicitly when there are PT1 or PT4 cannabis mutants available.…”
Section: The Correlation Between Cannabinoid Production and The Transcript Levels Of Corresponding Biosynthetic Genescontrasting
confidence: 76%
See 1 more Smart Citation
“…In general, PT1 and PT4 are similarly regulated during female flower maturation in the same variety but the regulation is temporally different. The superimposition suggests that PT1 instead of PT4 more correlates with CBG content, which is not consistent with the recent findings (Blatt-Janmaat & Qu, 2021). Further analysis of these two enzymes will be more explicitly when there are PT1 or PT4 cannabis mutants available.…”
Section: The Correlation Between Cannabinoid Production and The Transcript Levels Of Corresponding Biosynthetic Genescontrasting
confidence: 76%
“…PT1 was initially found to catalyze CBGA biosynthesis (Page & Boubakir, 2012). Recently PT4 was reported to have higher enzymatic activity (Blatt-Janmaat & Qu, 2021).…”
Section: The Correlation Between Cannabinoid Production and The Transcript Levels Of Corresponding Biosynthetic Genesmentioning
confidence: 99%
“…Of primary interest are the eponymous cannabis plant and the production of the euphoric drug tetrahydrocannabinol (THC) and other non‐psychoactive drugs, such as cannabidiol (CBD). The site of phytocannabinoid and terpene accumulation are the glandular trichomes present on the aerial tissue and in the highest density on female flowers (reviewed by Blatt‐Janmaat and Qu, 2021).…”
Section: Chalcone Isomerase Fold; Structure and Evolutionmentioning
confidence: 99%
“…Studies of the cannabinoid receptors have shown that endocannabinoids attenuate and suppress the perception of pain ( 8 , 9 ). Naturally, cannabinoids are produced from cannabis plants, with more than 100 cannabinoids identified ( 10 ). The main cannabinoids produced are tetrahydrocannabinol (THC) and cannabidiol (CBD), but in contrast to the highly psychoactive THC, CBD has virtually no psychoactive properties ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, cannabinoids are produced from cannabis plants, with more than 100 cannabinoids identified ( 10 ). The main cannabinoids produced are tetrahydrocannabinol (THC) and cannabidiol (CBD), but in contrast to the highly psychoactive THC, CBD has virtually no psychoactive properties ( 10 , 11 ). In people, there is evidence that CBD may be a useful treatment for various chronic pain conditions ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%